Coping Strategies Among Adolescents During the Covid-19 Pandemic: A Cross-Cultural Exploration - Maddaleno-Herrera, M (Elsevier Inc., 2024)
Purpose: To identify the patterns of stressors associated with the COVID-19 pandemic among adolescents living in different cultural settings and to explore how adolescents cope with such stressors, particularly by type of stressor, site, and gender. Methods: The study was based on focus group discussion data from 9 urban poor communities in Kinshasa (Democratic Republic of Congo), Blantyre (Malawi), Shanghai (China), Semarang and Denpasar (Indonesia), New Orleans (USA), Ghent (Belgium), São Paulo (Brazil), and Santiago (Chile). Translated transcripts from the focus group discussions were uploaded into ATLAS.ti (Version 9.1) and analyzed using an inductive thematic analytical approach to code and identify themes related to the primary objectives. Results: Adolescents in Blantyre and Kinshasa reported stressors primarily related to economic constraints and hardships, whereas adolescents in other sites were more likely to report stressors related to school lockdowns. Patterns of coping strategies also loosely aligned with these differences, as adolescents in Blantyre and Kinshasa were also more likely to report using religious coping strategies compared to any other site. Still, the most common coping mechanism mentioned across sites was obtaining social support, with support from friends and family being the most dominant. Discussion: A comprehensive understanding of adolescent stressors and coping mechanisms is valuable for promoting internal resources and positive outcomes for adolescents. Given that adolescents’ stressors and types of coping strategies varied primarily by socioeconomic factors, interventions that aim to bolster positive coping among adolescents need to consider the local context and available resources. © 2024 Society for Adolescent Health and Medicine